1999
DOI: 10.2307/3434342
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Crystalline Silica and Autoimmune Disease

Abstract: Occupational exposure to silica dust has been examined as a possible risk factor with respect to several systemic autoimmune diseases, including scleroderma, rheumatoid arthritis, systemic lupus erythematosus, and some of the small vessel vasculitidies with renal involvement (e.g., Wegener granulomatosis). Crystalline silica, or quartz, is an abundant mineral found in sand, rock, and soil. High-level exposure to respirable silica dust can cause chronic inflammation and fibrosis in the lung and other organs. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
114
1
17

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 68 publications
(119 reference statements)
1
114
1
17
Order By: Relevance
“…Occupational exposure to crystalline silica leads to silicosis, which is characterized by a progressive granulomatous and fibrogenic response in the lung (Ishihara et al 2001). Another well-known health outcome associated with silica exposure is an increase in the incidence of autoimmune disorders Parks, Conrad, and Cooper 1999) including rheumatoid arthritis (Rosenman, Moore-Fuller, and Reilly 1999), scleroderma (Martin et al 1999), systemic lupus erythematosus (Parks and Cooper 2006), and antineutrophilic cytoplasmic antibody-related nephritis (Tervaert, Stegeman, and Kallenberg 1998). Experimental exposure of crystalline silica is known to cause granuloma formation (Huang et al 2001;Kumar 1989;Langley et al 2004Langley et al , 2010Saffiotti and Stinson 1988) and/or fibrosis (Porter et al 2004) in the lungs of rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational exposure to crystalline silica leads to silicosis, which is characterized by a progressive granulomatous and fibrogenic response in the lung (Ishihara et al 2001). Another well-known health outcome associated with silica exposure is an increase in the incidence of autoimmune disorders Parks, Conrad, and Cooper 1999) including rheumatoid arthritis (Rosenman, Moore-Fuller, and Reilly 1999), scleroderma (Martin et al 1999), systemic lupus erythematosus (Parks and Cooper 2006), and antineutrophilic cytoplasmic antibody-related nephritis (Tervaert, Stegeman, and Kallenberg 1998). Experimental exposure of crystalline silica is known to cause granuloma formation (Huang et al 2001;Kumar 1989;Langley et al 2004Langley et al , 2010Saffiotti and Stinson 1988) and/or fibrosis (Porter et al 2004) in the lungs of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to crystalline silica is associated with silicosis, lung cancer, pulmonary tuberculosis, and chronic obstructive pulmonary disease (Calvert et al 2003). In addition, silicosis patients often develop autoimmune diseases Parks, Conrad, and Cooper 1999). It has been reported that experimental chronic exposure to crystalline silica caused granuloma formation (Huang et al 2001;Kumar 1989;Langley et al 2004Langley et al , 2010Saffiotti and Stinson 1988) and/or fibrosis (Porter et al 2004) in rats.…”
Section: Introductionmentioning
confidence: 99%
“…At high levels, silica results in silicosis, a condition characterized by radiographic changes, impaired pulmonary function, and increased risk of other respiratory diseases (4). Increased risks of autoimmune diseases, including systemic lupus erythematosus, rheumatoid arthritis, and scleroderma, have also been observed among occupational groups highly exposed to silica (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…13 Crystalline SiO 2 , occurring in several forms characterized by three-dimensional repeating patterns, is the cause of the pulmonary disease silicosis. 14,15 In contrast, amorphous SiO 2 , which has no significantly repeatable pattern, has minimal health risks to people.…”
Section: Discussionmentioning
confidence: 99%